Revision and resurrection of the genus name Mezammira Fieber, 1876 (Hemiptera: Cicadidae) with special focus on its species from Greece and the description of two new species - Gogala, Matija (Acta entomologica slovenica (Ljubljana), 2017)
Cicada species of the genus Mezammira Fieber, 1876, previously known as species of the genus Cicadivetta Boulard, 1982, Cicadetta Kolenati, 1857, Melampsalta Kolenati, 1857, Tettigetta Kolenati, 1857 or also Pauropsalta Goding & Froggatt, 1904, were investigated in Greece. Arguments for a resurrection of the older generic name Mezammira are provided. Since the type species of this genus, Mezammira flaveola comb. nova, is lost or destroyed, we selected and are describing in this paper a neotype from the locality on Mt. Taigetos, not far from the locus typicus Mistra, Sparta, Greece, mentioned by Brullé (1833). We are adding also a description of a female, never published yet in the literature. Till now in Greece the following species of this genus were known: Mezammira flaveola comb. nova, M. tibialis comb. nova, M. carayoni comb. nova and M. goumenissa comb. nova. In the present paper we are describing in addition two new species: one from Peloponnese, M. sakisi sp. nova and one from Naxos Island, M. filoti sp. nova. Some of the Greek Mezammira species have very limited distribution areas. Their calling song patterns are characteristic with high repetition of short echemes of at least two different durations. Two of the species, M. carayoni comb. nova and M. filoti sp. nova are, according to our present knowledge, endemic to the islands of Crete and Naxos respectively and are allopatric to other Mezammira species. Mezammira goumenissa comb. nova and M. sakisi sp. nova live in sympatry or at least parapatry with the widely distributed M. flaveola comb. nova in Southern Greece. This is probably the reason, that only these two species (M. goumenissa comb. nova and M. sakisi sp. nova) emit songs with the carrier frequency much higher than the remaining species, probably preventing acoustic interference.
Keywords: bioacoustics; bioakustika; Cicadidae; Cicadivetta; Grčija; Greece; Hemiptera; Mezammira; new species; škržadi